Estimates of horizontal fluxes of oxygen, heat, and salt in western Long Island Sound. Issue 10 (29th October 2014) - McCardell, Grant; O'Donnell, James
Abstract The dissolved oxygen (DO) concentration in the bottom waters of western Long Island Sound decreases to hypoxic levels between April and July. Since the rate of decline of DO is considerably less than measured respiration, there must be significant vertical transport of DO from oxygen richer waters near the surface and/or horizontal transport from the central Sound. Simple model budgets with either of these sources are able to provide predictions of the seasonal rate of decline that are consistent with the observed values. Although prior budget estimates indicated that vertical fluxes were a significant portion of the resupply of DO, these were not able to discount the possible importance of horizontal fluxes, nor have there been any measurements of horizontal fluxes in this region. We present an analysis of time series of moored conductivity, temperature, DO, and current observations in the hypoxic area of Long Island Sound during the summers of 2005 and 2006. We estimate the near‐bottom along‐channel flux divergences of salt, heat, and DO as 0.11 ± 0.08 g kg−1 d−1, −5 ± 6 W m−3, and 4 ± 6 μM d−1, respectively. Since this horizontal DO transport is only 25% of the magnitude of the mean rate of respiration, we conclude that vertical transport by mixing forms the bulk of the physical resupply of DO to the hypoxic zone of the western Sound.